Pediatric Psychogenic Non-Epileptic Seizures : A Treatment Guide - Caplan, Rochelle; Doss, Julia; Plioplys, Sigita; Jones, Jana E. (Springer International Publishing : Imprint: Springer, 2017)
This volume describes the basics for short- and long-term treatment of Psychogenic Non-Epileptic Seizures (PNES) in children. The text acknowledges that the disorder, though rare and highly morbid, is treatable when it is not misdiagnosed. Given the limited diagnostic and clinical training offered to clinicians, this book aims to equip professionals with the tools needed to improve the poor quality of life of youth with PNES. The text begins by introducing the main features of the disorder and the problems involved in diagnosing PNES in children. It then describes techniques to overcome these problems in order to make a reliable and valid diagnosis of PNES, as well as provide feedback on the diagnosis and treatment plan. The last section describes the indications for cognitive behavior therapy for youth with PNES and suggested treatment paradigms. Incorporation of do's and don'ts and their relevant clinical examples in all sections of the proposed guide provide the reader with skills and techniques. The book also includes an appendix with resources for parents, children, and school nurses and teachers, relaxation techniques for the child and parents, templates of letters for the child's school about the condition and behavior management plan, templates of supporting letters from epileptologists and primary care physicians, CBT treatment paradigm, and information on individual supervision, workshops and webinars. Written by the few experts in this area, Pediatric Psychogenic Non-Epileptic Seizures is the ultimate guide for psychiatrists, psychologists, nurses, primary care physicians, neurologists, epileptologists, social workers, nurses, school counselors, and all medical professionals working with children experiencing seizures.